2019
DOI: 10.1097/md.0000000000017411
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive drugs use over a 5-year period among children and adolescents in Beijing, China

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Ma et al [6] stated that β-Blocker prescribing during outpatient visits for uncomplicated hypertension was high and increased modestly from 24% in 1993 to 33% in 2004 in the United States [6]. Wu et al [7] reported that among children and adolescents in Beijing, China the trends of prescribing beta-blockers increased from 2010 to 2014 and that beta-blockers and angiotensinconverting enzyme inhibitors were more likely to be prescribed in outpatient visits [7]. Ahmed et al [8] reported that about 18.66% of the antihypertensive classes that were used in the outpatient setting were beta-blockers [8].…”
Section: Between 1 Stmentioning
confidence: 99%
“…Ma et al [6] stated that β-Blocker prescribing during outpatient visits for uncomplicated hypertension was high and increased modestly from 24% in 1993 to 33% in 2004 in the United States [6]. Wu et al [7] reported that among children and adolescents in Beijing, China the trends of prescribing beta-blockers increased from 2010 to 2014 and that beta-blockers and angiotensinconverting enzyme inhibitors were more likely to be prescribed in outpatient visits [7]. Ahmed et al [8] reported that about 18.66% of the antihypertensive classes that were used in the outpatient setting were beta-blockers [8].…”
Section: Between 1 Stmentioning
confidence: 99%
“…Studies from a range of countries showed that the use of antihypertensive medicines has increased steadily over recent decades [22][23][24][25][26]. The decrease in CVD mortality in Europe that has been observed in recent years is attributed to active preventive practices and proper treatment [27,28].…”
Section: Introductionmentioning
confidence: 99%